2016
DOI: 10.1038/nrendo.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Healthy ageing, the genome and the environment

Abstract: The sequenced genomes of individuals aged ≥ 80 years, who were highly educated, self referred volunteers and with no self reported chronic diseases were compared to young controls. In these data, healthy ageing is a distinct phenotype from exceptional longevity and genetic factors that protect against disease might be enriched in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Second, despite different definitions and opinion regarding the concept of healthy aging, the clinical and biochemical data on centenarians showed that they can be considered as a paradigm of healthy aging as they avoid or largely postpone all major age-related diseases ( Andersen et al, 2012 ). Thus, healthy aging and exceptional longevity (people who live more than 100 years) are deeply related ( Christensen and McGue, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, despite different definitions and opinion regarding the concept of healthy aging, the clinical and biochemical data on centenarians showed that they can be considered as a paradigm of healthy aging as they avoid or largely postpone all major age-related diseases ( Andersen et al, 2012 ). Thus, healthy aging and exceptional longevity (people who live more than 100 years) are deeply related ( Christensen and McGue, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 Gene Loc = location of CpG site relative to coding gene. 4 CGI = CpG island. 5 IGR = Intergenic region.…”
Section: Evaluation Of Epigenetic Changes In Individuals With Long and Short Durations Of Schoolingmentioning
confidence: 99%
“…Biological and social environmental factors influence the development and life expectancy of the average human being [1,2]. The current investigations are centered on the impact of different environmental exposures at different stages of life, including those involved in aging and the manifestation of age-related diseases [3][4][5][6][7]. In this sense, studies have identified a crosslink between early-life adverse conditions and the reduction of life expectancy and "healthspan" [8].…”
Section: Introductionmentioning
confidence: 99%
“…Besides genetic and lifestyle factors, environmental (climate) conditions are relevant modulators of mortality and associated life expectancy [1][2][3][4][5]. Environmental conditions, i.e., barometric pressure, partial pressure of oxygen, temperature, ultra-violet (UV) radiation, and air pollution, change characteristically with varying altitudes [6].…”
Section: Introductionmentioning
confidence: 99%